2022
DOI: 10.1111/1756-185x.14283
|View full text |Cite
|
Sign up to set email alerts
|

Association between Klebsiella pneumoniae and ankylosing spondylitis: A systematic review and meta‐analysis

Abstract: Aim The aim of this study is to evaluate the association between Klebsiella pneumoniae infection and ankylosing spondylitis (AS). Method Five electronic databases, PubMed, Embase, Medline, Web of Science, and Scopes, were searched until September 29, 2021. Cohort and case‐control studies that assessed the association between K. pneumoniae infection and AS were included. Pooled odds ratio (OR) was selected to show the effect size. Subgroup analysis (active or inactive AS) and 2 forms of sensitivity analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…pneumoniaeinfecesofpatientswithAS. 13 However, K. pneumoniae has not been demonstrated to cause AS-like phenotype in animal models. IgA antibodies to K. pneumoniae derived from AS patients may be used as probes to identify serotypes of…”
Section: Edito Lmentioning
confidence: 99%
See 1 more Smart Citation
“…pneumoniaeinfecesofpatientswithAS. 13 However, K. pneumoniae has not been demonstrated to cause AS-like phenotype in animal models. IgA antibodies to K. pneumoniae derived from AS patients may be used as probes to identify serotypes of…”
Section: Edito Lmentioning
confidence: 99%
“…The similar approaches by Chriswell et al 11 and other studies in RA can be adopted to investigate the bacterial association with ankylosing spondylitis (AS), another inflammatory arthritis with high suspicion of bacteria as a trigger. A meta‐analysis reports presence of IgA and IgG antibodies against Klebsiella pneumoniae in serum and presence of K. pneumoniae in feces of patients with AS 13 . However, K. pneumoniae has not been demonstrated to cause AS‐like phenotype in animal models.…”
mentioning
confidence: 99%
“…Self-reactive T cells with poor immunological synapse formation may be able to circumvent negative selection in the thymus, where self-antigen expression is exceedingly low, owing to the extremely low expression of selfantigens. Numerous self-and foreign-antigen peptides have been analyzed and sequenced in the past, but there is no evidence that any of these peptides are cross-reactive (19). In addition, Taurog et al observed that clinical symptoms manifested in HLA-B27/Hu2m transgenic rats lacking functional CD8+ T cells (20,21).…”
Section: The Role Of Hla-b27 In Asmentioning
confidence: 99%
“…Early results suggested Klebsiella pneumoniae , a Gram-negative bacterium causing pneumonia and sepsis, as a potential candidate. It was first related to AS development due to its fecal carriage and increased serum antibody levels compared to those in HLA-B27-negative patients ( 15 ). Then members from Enterobacteriaceae including Yersinia , Salmonella , and Shigella are considered as potential candidates for causing typhoid fever and sequelae of arthritis.…”
Section: Cause Of As: Infection or Danger?mentioning
confidence: 99%